2014
DOI: 10.6061/clinics/2014(11)01
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphism in the serotonin transporter gene-linked polymorphic region and response to serotonin reuptake inhibitors in patients with premature ejaculation

Abstract: OBJECTIVES:Serotonin plays a central role in ejaculation and selective serotonin reuptake inhibitors have been successfully used to treat premature ejaculation. Here, we evaluated the relationship between a polymorphism in the serotonin transporter gene-linked polymorphic region (5-HTTLPR) and the response of patients with premature ejaculation to SSRI medication.METHODS:Sixty-nine premature ejaculation patients were treated with 20 mg/d paroxetine for three months. The Intravaginal Ejaculatory Latency Time an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Therefore, 5-HT was considered an anorexigenic neurotransmitter and has become a target for anti-obesity treatment. 73…”
Section: Dovepressmentioning
confidence: 99%
“…Therefore, 5-HT was considered an anorexigenic neurotransmitter and has become a target for anti-obesity treatment. 73…”
Section: Dovepressmentioning
confidence: 99%
“…Pharmacogenetic studies of SSRI efficacy for this indication may provide insight into SSRI tolerability in patients treated for more traditional indications. In 69 patients with premature ejaculation treated with paroxetine, the 5‐HTTLPR S allele was more common in responders (i.e., more frequent delayed ejaculation, p<0.05) . To the contrary, in a study of 54 Dutch men with premature ejaculation treated with paroxetine, 5‐HTTLPR genotype was not associated with fold change in intravaginal ejaculator latency time (p=0.83) …”
Section: Resultsmentioning
confidence: 98%
“…In 69 patients with premature ejaculation treated with paroxetine, the 5-HTTLPR S allele was more common in responders (i.e., more frequent delayed ejaculation, p<0.05). 46 To the contrary, in a study of 54 Dutch men with premature ejaculation treated with paroxetine, 5-HTTLPR genotype was not associated with fold change in intravaginal ejaculator latency time (p=0.83). 47 It is not surprising that results for this phenotype are conflicting, as sexual functioning is a complex phenotype, with potential for dysfunction in desire, arousal, orgasm, or satisfaction.…”
Section: Sexual Dysfunction Adverse Eventsmentioning
confidence: 94%
“…Regarding the treatment of SSRIs in LPE, Janssen et al [ 25 ] investigated the association between the 5-HTTLPR polymorphism and the response to paroxetine in men with LPE, reporting no difference in 5-HTTLPR allelic and genotypic variations. Ozbek et al [ 26 ] evaluated the association between the 5-HTTLPR polymorphism and 20-mg paroxetine-induced ejaculation delay in LPE patients. The study showed the S allele was significantly more frequent in responders.…”
Section: Discussionmentioning
confidence: 99%